ENERGY SECURITY AND NATIONAL STRATEGIES - Komilov Shahboz (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the concept of energy security and its significance within national development strategies. Energy security is analyzed in terms of reliable energy supply, affordability, sustainability, and resilience to external and internal risks. The study explores key national strategies aimed at ensuring energy security, including diversification of energy sources, development of renewable energy, energy efficiency policies, and international cooperation. The article highlights the role of strategic planning in strengthening national energy systems and supporting long-term economic and environmental stability.